Regional powers as protagonists of the International Political System: Cooperation and dialogue within the BRIC Forum - Morales Ruvalcaba, Daniel Efrén; Rocha Valencia, Alberto; Vargas García, Elizabeth (Geopolítica(s). Revista de estudios sobre espacio y poder, 2014)
While regional powers started to play relevant geo-economic and geopolitical roles in the international relations system in the 1990s, it was not until the 2000s when they reached out even more outstanding positions. The fact that they had begun an ascending process in the pyramid of world political power became simply obvious. Since then, these regional powers started to come closer, to converge and cooperate, thereby moving towards the construction of an international forum: the BRIC Forum. Very early in this process, this Forum became a first-class collective international actor, together with the G-20 and in competition with the G-7. This article deals with the (semi-peripheral) constitutive nature and structural position of the rising regional powers within the BRIC Forum. Likewise, we will examine each of the Forum’s summits and the geopolitics that has been fostered by the BRIC countries. According to our analysis, there is evidence that all members of the Forum are called to play important roles in the processes of change and transformation in the international political order of the 21st century.
Keywords: International Political System; BRIC; regional powers; geopolitics; semi-periphery